THE STRATEGY ANALYSIS FOR PATROL ELEMENTS ADDITION OF BRAVO NAVAL BASE TO SUPPORT MARINE SECURITY OPERATIONS AT INDONESIA ARCHIPELAGIC SEA LANES I - Manahan Budiarto Pandjaitan; Gunardi Gunardi; Panji Suwarno (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
Indonesian Navy is tasked with enforcing the law and maintaining security in the national jurisdictional sea area following the provisions of national law and international law that have been ratified. To carry out these basic tasks to run well, it is necessary to have support from the Naval Base which is quite accommodating in terms of service and logistical support. The problem in this research is how to compile the strategy analysis for patrol elements addition of Bravo Naval Base to support marine security operations at Indonesia Archipelagic Sea Lanes 1. The purpose of this study was to determine the optimum function of the patrol element of base owned by Bravo Naval Base in support of marine security operations in the Indonesian Archipelago Sea Lanes 1. The method used in this study is Qualitative Descriptive methods by NVivo Software and SWOT analysis methods. The results of this study are the continuation strategies analysis for patrol elements addition of Bravo Naval Base to support marine security operations, and it needs to be a concern and needs to be improved by Indonesian Navy.Keywords: Strategy Analysis, Patrol Element Additions, Bravo Indonesia Naval Base.